THE MECHANISM FORMATION OF COMPANY’S INNOVATION POLICY AS THE INDUSTRY’S DEVELOPMENT STRATEGY - Lozhachevska, Olena; Kovalenko, Olga (Proceedings of National Aviation University (archive), 2017)
Purpose: forms its own innovation policy, focusing on innovation policy, which defines priority directions of NTP and provides support own interests and resource capabilities and needs of the market. Methods: To study the innovation policy was used combining technical goals and policy investments and focused on new technologies and products. Innovation policy involves research facilities identified in which the company is trying to promote the first systematic search for new technological opportunities. Results: Development of innovative enterprise policy involves determining the goals and strategies of development in the near future and prospects based on the evaluation of the enterprise potential and its supply of appropriate resources. In practice, the formation of scientific and technical enterprise policy decision on the basis of a new product (the transition to new technology) is a difficult task – how in technical, organizational, and in commercial terms. Discussion: The constant changing market environment factors and customer needs, accelerate NTP developed countries on the one hand makes it difficult, on the other – pushing becomes a prerequisite of conscious innovation policy Ukrainian enterprises.